2021
DOI: 10.1044/2021_jslhr-21-00047
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Reproducibility of Meta-Analysis in Speech, Language, and Hearing Research

Abstract: Purpose The purposes of this meta-review are to (a) articulate the importance of transparency and reproducibility in meta-analysis, (b) assess the transparency and reproducibility of meta-analyses published in journals of the American Speech-Language-Hearing Association (ASHA), and (c) discuss the implications of our findings and recommendations for future research. Method We conducted a meta-review of all meta-analyses published in ASHA journals throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Stage 3: Presenting and Interpreting Results. As shown in Table 3, when presenting, interpreting, and discussing results, high-quality systematic reviews (a) organize findings to address research questions, (b) summarize results, (c) ground interpretations and conclusions in the data (Chow et al, 2021;Shamseer et al, 2015;Talbott et al, 2018), (d) link back to the review's aims, and (e) interpret results in context (Wilson & Anagnostopoulos, 2021). As an exemplar, Cumming et al (2020) systematically reviewed associations between school-based experiences and student executive function (EF) development.…”
Section: Contextmentioning
confidence: 99%
“…Stage 3: Presenting and Interpreting Results. As shown in Table 3, when presenting, interpreting, and discussing results, high-quality systematic reviews (a) organize findings to address research questions, (b) summarize results, (c) ground interpretations and conclusions in the data (Chow et al, 2021;Shamseer et al, 2015;Talbott et al, 2018), (d) link back to the review's aims, and (e) interpret results in context (Wilson & Anagnostopoulos, 2021). As an exemplar, Cumming et al (2020) systematically reviewed associations between school-based experiences and student executive function (EF) development.…”
Section: Contextmentioning
confidence: 99%
“…Future meta-analysis investigations should incorporate methodology that is suitable not only for transparency and reproducibility (Chow et al, 2021) but also for the small sample sizes and heterogenous data reported by primary studies. Although previous meta-analyses in the field have included moderator analyses, only a few prior syntheses (e.g., Sandbank et al, 2020) have incorporated these advanced methods.…”
Section: Conducting Meta-analysesmentioning
confidence: 99%
“…Regarding the reporting of information from clinical trials, there is a need for clear and explicit reporting of demographic characteristics, as is advocated for by meta‐analytical researchers (Chow et al, 2023). To improve the ability of researchers to consider what interventions are working best and for whom, it is essential to provide detailed information on study participants.…”
Section: Discussionmentioning
confidence: 99%